Optimalisasi Pembelajaran TPQ melalui Media Flashcard: Sebuah Pendekatan Kreatif - Bimantara, Andika Rendra; Shyahida, Kamia Rahmanintya; Triwijayanti, Adinda Zahra; Antariksa, Risma Aisah; Sukri, Nawal Rasid; Musyarofah, Annisa Hidayatul; Suprapto, Damara Inas; Zahra, Dalia; Maharani, Sabela Firda; Nazlah, Nazlah; Azzahra, Athifa; Aulia, Atha (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Searching for research titles and abstracts is made easy with these key word A key element in creating a Qur'anic generation with an accurate knowledge of Islam is raising the proficiency of Qur'anic Education Park (TPQ) teachers. Using engaging and interactive learning materials is one of the best ways to raise the standard of education. This study is going to explore how well flashcard media with daily prayers can improve TPQ teachers' proficiency, particularly in terms of making the subject easier and more enjoyable for students to learn. The research method adopted is action research, involving both qualitativ approaches. The subjects of the research were TPQ teachers from various Islamic educational institutions. To assess the competence increase before and after flashcard use, data were collected via observation, interviews, and questionnaires. The findings showed that employing flashcards can enhance teachers' comprehension and abilities to provide daily prayers in a more systematic and effective manner. Moreover, this approach enhances students' interest in learning, making the learning process more interactive. Therefore, flashcard media can operate as an innovative option for learning daily prayers at TPQ and can help in the development of a more qualified Qur'anic generation. This study suggests that the design and variety of learning media should be further developed to enhance teaching effectiveness in TPQ. The results of the study showed an increase in the average teacher competency score from 62,5 to 85,3 after the use of flashcards (an increase of 36.48%). Therefore, flashcards can be an innovative choice for teaching daily prayers at TPQs and can help develop a higher quality Qur'anic generation. This study also confirms the role of visual learning media in supporting the religious learning process, especially in early childhood religious education.